2016
DOI: 10.5539/jfr.v6n1p69
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Some Trace Elements in Vegetables Sold at Maun Market, Botswana

Abstract: Contamination of vegetables with toxic metals is one of the most important contributing factors to ill health throughout the world, more so because vegetables are considered essential for human health and their consumption is highly recommended by health authorities. The aim of this study was to determine the concentrations of selected essential elements (Fe, Cu, Mn, Mo, Zn) and toxic elements (As, Cd, Cr, Pb) in common vegetables sold for human consumption in supermarkets and open market of Maun village, Bots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
3
1
1
Order By: Relevance
“…The presence of Zn in the vegetables could be associated with the use of wastewater for irrigation, contaminated soil and fertilizers and pesticides used in vegetable growing. Results in this study indicated lower zinc levels when compared with those recorded in a previous study (23.8 -89.8 mg/kg) carried out in Maun market, Botswana (Bati et al, 2016). Lower values of Zn (3.77 -16.3 mg/kg) than those obtained in this study were reported in a previous study in Banat County, Romania (Harmanescu et al, 2011).…”
Section: Resultscontrasting
confidence: 58%
“…The presence of Zn in the vegetables could be associated with the use of wastewater for irrigation, contaminated soil and fertilizers and pesticides used in vegetable growing. Results in this study indicated lower zinc levels when compared with those recorded in a previous study (23.8 -89.8 mg/kg) carried out in Maun market, Botswana (Bati et al, 2016). Lower values of Zn (3.77 -16.3 mg/kg) than those obtained in this study were reported in a previous study in Banat County, Romania (Harmanescu et al, 2011).…”
Section: Resultscontrasting
confidence: 58%
“…According to Kabata-Pendias and Mukherjee (2007) manganese content in tuber dry matter ranges from 4 to 15 mg kg -1 , in research by Sawicka et al (2016) and Bati et al (2017) the respective ranges were 6.3-17.3 and 17.2 mg kg -1 , and in the studies by Mahamud et al (2015) conducted in USA and Bangladesh it was significantly affected by the cultivar and ranged from 7.4 to 50.6 mg kg -1 . In the experiment reported here, the tuber content of manganese was from 20.01 to 22.02 mg kg -1 and was significantly influenced by cultivars, herbicides applied alone or combined with biostimulants as well as moisture and thermal conditions during the study period ( Table 7).…”
Section: Manganese Content and Uptakementioning
confidence: 96%
“…That observation is related to the pillars of ecological agriculture -no use of industrialized fertilizers and pesticides (which constitute typical sources of As contamination) (Bati et al 2017).…”
Section: Trace Elements In Biomassesmentioning
confidence: 99%
“…França et al (2017) reported a signi cant increase in Cd, Pb, Ni and Zn concentrations in plants growing in the metropolitan region of Recife City, Pernambuco State, Brazil. Those authors noted that the high levels of those elements in plants were related to particulate emissions in the atmosphere that spread those contaminants to the air, water, and cultivated soils(França et al 2017), as they can be such as organic matter and chemical fertilization and/or through the use of agrochemicals (fertilizers and agricultural defensive products)(Bati et al 2017;Radulescu et al 2013). The constant monitoring of trace elements in plant material derived from urban gardens will therefore be necessary to minimize public health risks(Alfaro et al 2017).…”
mentioning
confidence: 99%